2023
DOI: 10.3928/01484834-20220912-14
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Primary Care Track in Prelicensure Nursing Education

Abstract: Background: RNs practicing in primary care (PC) increase access to health care and contribute to better patient outcomes and cost savings, yet undergraduate nursing education traditionally focuses on disease-oriented care. This article describes a curricular track for infusing PC prelicensure programs. Method: PC content is threaded across four semesters with targeted assignments and clinical experiences. Providing clinical immersion experiences with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Students in both the Hawkins study and this study reported positive feedback and increased insight into the role of RNs in primary care through class assignments and clinical rotations. In addition, both Hawkins et al (2022) and this study had a similar impact on employment outcomes of graduating nursing students; many were offered employment in primary care and/or medically underserved community settings where they completed their practicum clinical rotations.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Students in both the Hawkins study and this study reported positive feedback and increased insight into the role of RNs in primary care through class assignments and clinical rotations. In addition, both Hawkins et al (2022) and this study had a similar impact on employment outcomes of graduating nursing students; many were offered employment in primary care and/or medically underserved community settings where they completed their practicum clinical rotations.…”
Section: Discussionmentioning
confidence: 83%
“…An educational innovation project was conducted by Hawkins et al (2022) that used course evaluations to report student feedback after creating a primary care track in prelicensure nursing education. Students in both the Hawkins study and this study reported positive feedback and increased insight into the role of RNs in primary care through class assignments and clinical rotations.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, we would also Study quality was appraised for each article (File S2). Most studies were rated as good quality, while one study was rated poor: a quality improvement/educational intervention study that did not present study aims or a research question and did not address alternative explanations of results or any unanticipated outcomes (Hawkins et al, 2022). Health equity content was categorized based on the CSDH framework categories (Solar & Irwin, 2010).…”
mentioning
confidence: 99%
“…Wihlborg and Avery (2021) evaluated syllabi from 24 out of all 25 Swedish undergraduate nursing programs. The remaining studies (n = 7) evaluated the presence of health equity content using student and/or faculty surveys(Buchanan & O'Connor, 2020;Foronda et al, 2020;Roy et al, 2022;Saini et al, 2022), course evaluations(Hawkins et al, 2022), preceptor evaluations(Hawkins et al, 2022), and interviews(Brown et al, 2023;Ercan-Şahin & Aslan, 2020). four semesters of courses,Hawkins et al (2022) reported that students expressed positive feedback, thought content was current and relevant, found practicum experiences to be positive, applied SDOH knowledge in those experiences, and that preceptors expressed satisfaction with students.…”
mentioning
confidence: 99%
See 1 more Smart Citation